Mucoadhesive Polymeric Hydrogels for Nasal Delivery of Penciclovir - Arindam Das, Prof. B. K. Gupta, Bhole Nath (Journal of Applied Pharmaceutical Science)
The study evaluated different mucoadhesive polymeric hydrogels for nasal delivery of penciclovir . Gels containing poly-N-vinyl-2-pyrrolidone (PVP) were prepared with crosslinking achieved by irradiation with a radiation dose of 15 kGy being as efficient as 20 kGy. Gels containing chitosan and carbopol were also evaluated. The mucoadhesive properties of gels were measured by a modification of a classical tensile experiment, employing a tensile tester and using freshly excised sheep nasal mucosa. Considering the mucoadhesive force, chitosan gel and gel prepared with 3% PVP in presence of polyethylene glycol (PEG) 600 were the most efficient. The in vitro drug release depended on the gel composition. Higher release rates were obtained from PVP gels compared to chitosan or carbopol gels. The release rate of drug from PVP gels was increased further in presence of PEG or glycerol. Histopathological investigations proved that the PVP was a safe hydrogel to be used for mucosal delivery. The PEG in gel formulations caused less damages to the nasal mucosal compared to formulation containing glycerol.
Keywords: Penciclovir nasal, nasal mucoadhesion, poly-N-vinyl-2- pyrrolidone hydrogels, chitosan nasal, carbopol nasal.